2021
DOI: 10.3390/foods10081876
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Foams in Vacuum Drying Processes. Effects of Interactions between Sugars, Proteins, and Surfactants on Foam Stability and Dried Foam Properties

Abstract: The hypothesis was that saccharides mediate interactions between surface-active components and that this will have an impact on foam decay during the drying process. Static light scattering was performed to determine changes in interactions between the foam stabilizer on a molecular level. Furthermore, pendant drop and oscillating drop measurements were performed to examine the surface tension and surface rheology. Foams were dried in conventional dryers as well as microwave-supported vacuum dryers. Final foam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 65 publications
(113 reference statements)
0
6
0
Order By: Relevance
“…The convective hot air + microwave‐assisted foam mat drying of powders has a superior property in bulk density which is important for packaging, storage, and transportation (Çalışkan Koç & Yüksel, 2020). In another study, it is reported that microwaved supported vacuum dried samples showed more indications for foam decay compared to conventional vacuum dried samples (Kubbutat et al, 2021). It has been determined that the microwave drying method is more efficient in terms of the drying time of the foams compared to the hot air drying method (Varhan et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The convective hot air + microwave‐assisted foam mat drying of powders has a superior property in bulk density which is important for packaging, storage, and transportation (Çalışkan Koç & Yüksel, 2020). In another study, it is reported that microwaved supported vacuum dried samples showed more indications for foam decay compared to conventional vacuum dried samples (Kubbutat et al, 2021). It has been determined that the microwave drying method is more efficient in terms of the drying time of the foams compared to the hot air drying method (Varhan et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Foam mat drying has been hybridized by replacing hot air drying with other drying methods to minimize the negative effects of hot air drying on product quality and drying characteristics. Several studies are highlighted that drying samples by hybridizing foam mat drying with advanced dehydration techniques such as freeze drying, microwave drying and vacuum drying has a positive effect on drying kinetics and quality parameters (Qadri et al, 2019; Kubbutat et al, 2021). Various research groups have looked at the drying kinetics of foam mats using thin‐layer modeling to determine which model best suits the drying process.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations